Utilizing GIS, remote sensing, and AHP-multi-criteria decision analysis for optimal landfill site selection in Kenitra Province, Morocco: a step towards sustainable development goals - Adil Moumane; Jamal Al Karkouri; Mouhcine Batchi (Discover Environment)
Abstract The aim of this study is to identify suitable landfill sites in Kenitra Province, Morocco, using ArcGIS 10.8, Remote Sensing, and the Analytic Hierarchy Process (AHP) to enhance site selection and improve environmental and public health outcomes. Additionally, the study seeks to enhance decision-making through multicriteria analysis, align landfill site selection with Sustainable Development Goals (SDGs) to promote long-term sustainability, and provide a model that can be replicated in other Moroccan regions or countries facing similar waste management challenges. Ten criteria were considered in selecting new landfill sites, including distance from surface water, soil permeability, land use land cover (LULC), topographic wetness index, distance from the shoreline, slope, aspect, proximity to urban areas, transportation networks, and villages. Maps for each criterion were generated, and pairwise comparisons were used to assign weights to these factors. A Weighted Overlay Analysis (WOA) was then applied to create a landfill suitability map, classifying areas into high, moderate, low, and unsuitable categories. The results reveal a limited availability of highly suitable landfill areas within the province. To address this, the study proposes two strategically located waste management sites, A and B, to mitigate land constraints. Establishing these sites as centralized landfills for multiple municipalities aligns with Sustainable Development Goals (SDGs) 3, 6, 14, 15, and 17, promoting public health, preventing water pollution, protecting ecosystems, and fostering partnerships for sustainable waste management. This comprehensive approach emphasizes the need for collaboration in achieving long-term sustainability and environmental conservation.